Human T Cell Differentiation Negatively Regulates Telomerase Expression Resulting in Reduced Activation-Induced Proliferation and Survival - Patrick, Michael S.; Cheng, Nai-Lin; Kim, Jaekwan; An, Jie; Dong, Fangyuan; Yang, Qian; Zou, Iris; Weng, Nan-ping (Frontiers in Immunology, 2019)
Maintenance of telomeres is essential for preserving T cell proliferative responses yet the precise role of telomerase in human T cell differentiation, function and aging is not fully understood. Here we analyzed human telomerase reverse transcriptase (hTERT) expression and telomerase activity in six T cell subsets from 111 human adults and found that levels of hTERT mRNA and telomerase activity had an ordered decrease from naïve (TN) to central memory (TCM) to effector memory (TEM) cells and were higher in CD4+ than their corresponding CD8+ subsets. This differentiation-related reduction of hTERT mRNA and telomerase activity was preserved after activation. Furthermore, the levels of hTERT mRNA and telomerase activity were positively correlated with the degree of activation-induced proliferation and survival of T cells in vitro. Partial knockdown of hTERT by an anti-sense oligo in naïve CD4+ cells led to a modest but significant reduction of cell proliferation and increase of apoptosis. Finally, we found that activation-induced levels of hTERT mRNA and telomerase activity in naïve CD4+ T cells were significantly lower in old than in young subjects. These findings reveal that hTERT/telomerase expression declines during T cell differentiation and age-associated reduction of activation-induced expression of hTERT/telomerase mainly affect naïve CD4+ T cells and suggest that enhancing telomerase activity could be a strategy to improve T cell function in the elderly.